Exploring the effect of service quality on repeat purchase intention, - Molepo, Patience (The IIE, 2022)
There is a high demand for higher education in South Africa & public institutions alone do not have capacity. This has seen a rise in private higher learning institutions to address this gap, resulting in higher levels of competition. Therefore, private higher learning institutions must explore new ways to gain a competitive edge and the popularity of concepts such as customer service and service quality in the business world has become a priority for the private higher learning sector. The researcher employed a quantitative, descriptive, cross-sectional, and deductive study. All data was collected at a single point in time using an online self-administered survey. This approach is convenient and effective as it takes into consideration the limitations of time and budget. A Likert scale was used to measure the degree of agreement and disagreement with questions posed to the participant. The SERVQUAL model is a widely used service quality model and adaptive to situations. All five dimensions work as a collective but should be prioritised based on consumer needs. Of the five dimensions, in the private higher learning sector, reliability, responsiveness, assurance, and empathy are of high importance in terms of students’ satisfaction and the service quality of the institution.
Keywords: Service delivery; Buying behavior; Private higher education; Brand loyalty